1999
DOI: 10.1590/s0100-879x1999001000017
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning reduces peripheral oxidative damage associated with brain ischemia in rats

Abstract: Brain ischemia followed by reperfusion causes neuronal death related to oxidative damage. Furthermore, it has been reported that subjects suffering from ischemic cerebrovascular disorders exhibit changes in circulating platelet aggregation, a characteristic that might be important for their clinical outcome. In the present investigation we studied tert-butyl hydroperoxide-initiated plasma chemiluminescence and thiol content as measures of peripheral oxidative damage in naive and preconditioned rats submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The lack of correlation between the changes of thiols in plasma and brain in MCAO and BCAO suggests that different mechanisms are involved in the regulation of these redox systems. Previously, it was hypothesized that the main factor that contributes to reducing plasma SH is the formation of ROS in the brain tissue in the reperfusion phase [11]. However, it was later shown that endothelial dysfunction of peripheral vessels plays the leading role in the generalization of oxidative stress during cerebral ischaemia [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of correlation between the changes of thiols in plasma and brain in MCAO and BCAO suggests that different mechanisms are involved in the regulation of these redox systems. Previously, it was hypothesized that the main factor that contributes to reducing plasma SH is the formation of ROS in the brain tissue in the reperfusion phase [11]. However, it was later shown that endothelial dysfunction of peripheral vessels plays the leading role in the generalization of oxidative stress during cerebral ischaemia [6].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that global cerebral ischaemia-reperfusion causes a rapid and continuous (up to 10-30 days) decrease in sulfhydryl (SH) groups and an increase in the products of lipid peroxidation in rat plasma [11]. Concomitantly, the total content of thiol groups may not reflect the full dynamics and intensity of oxidative stress, because of the contribution of albumin, which has a lifetime of about 20 days and an abnormally low pK (∼5) for its free SH group [12].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the TRAP values in plasma were significantly increased after 15 min of ischaemia, remained high at early (3 h) reperfusion and decreased significantly at the end of later (72 h) reperfusion. Indeed, recent studies have provided evidence that under pathologic conditions such as cerebral I/R, the antioxidant systems of plasma (Frassetto et al 1999) and brain have been changed (Hosseinzadeh and Sadeghnia 2005). Other studies demonstrated in different brain areas significantly decreased activities and levels of both non-enzymatic antioxidants like reduced glutathione (Nita et al 2001) and enzymatic antioxidants like superoxide dismutase (Aabdallah and Eid 2004), catalase (Homi et al 2002), glutathione reductase, glutathione-Stransferase and glutathione peroxidase (Ahmad et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia or brain trauma causes systemic disturbances in metabolism involving the peripheral vessels that induce a massive release of ROS, particularly of superoxide anion, which is apparently the result of activation of the sympathoadrenal system [7,8]. This is the most obvious reason for the rapid decrease in the level of reduced aminothiols and in the level of total blood plasma sulfhydryl groups [19,46]. However, there is still no clear understanding of the role of systemic OS in the pathogenesis of ischemic brain damage and the prospects for using systemic OS as a therapeutic target in stroke.…”
Section: The Effect Of Npts On Aminothiolsmentioning
confidence: 99%